Analyzing the Foreign Policy of Microstates: The Relevance of the International Patron-Client Model. Issue 3 (1st February 2016) - Veenendaal, Wouter P.
Abstract: The position of small states in international relations is traditionally described in terms of vulnerability and dependence. This dominant perspective is largely incomplete and inaccurate, because it disregards the element of exchange that characterizes the international linkages between many small and large states. In this article, I aim to outline and motivate an alternative model on the basis of which such relationships can be understood, which has been referred to as the international patron–client framework. After providing an overview of the contemporary academic literature on the role of small states in international politics, two sections follow in which I motivate the applicability of the patron–client framework to the field of international relations, and in which I explain the motives of both patron and client states. Subsequently, the accuracy and usefulness of the framework is examined on the basis of interview data gathered during field research in the three small client states of St. Kitts and Nevis, Seychelles, and Palau. The findings of this analysis indicate that the patron–client linkage offers a more fruitful model to study the relations between small and large states than the existing literature does, because it recognizes the element of exchange that such relationships entail.